A descriptive study of financial wellness influencing factors among Malaysian: examining the moderating effect of personality - Wan Nor Fatihah Wan Hanafi (2015)
This project paper attempts to identify two factors influencing financial wellness among Malaysian people, which are Literacy and Social Status with the effect of personality factor as an enhancement. Financial Wellness is a term used to describe the level of financial health of a person. An individual with a fine financial wellness will be free from financial worries and enjoy a more comfortable life. The empirical evidence from many literatures witnessed that the independent variables (Literacy and Social Status) have significant effect to the variable (Financial Wellness). So, the primary focus of this paper is the attempt to study whether personality could enhance both the independent variables to influence the dependent variable. This is crucial since the study has not been greatly carried out in Malaysia. The aims of this present study are threefold: firstly is to determine the influential factors of financial wellness among Malaysian, to examine the response towards financial wellness in terms of demographic profile, and finally to identify the moderating effect of personality between literacy and social status towards financial wellness. An inferential analysis is employed to test the relationship among selected variables. After conducting this research, the results indicate that both Literacy and Social Status have significant relationship with Financial Wellness. Nevertheless, Personal Attributes had no effect to moderate literacy and social status towards financial wellness and also not significant to stand alone as an independent variable to influence financial wellness.